A randomized controlled multicenter trial of individual placement and support for patients with moderate-to-severe mental illness - Reme, Silje E.; Monstad, Karin; Fyhn, Tonje; Sveinsdottir, Vigdis; Løvvik, Camilla; Lie, Stein Atle; Øverland, Simon (Scandinavian Journal of Work, Environment & Health, 2019)
' ' OBJECTIVES ': 'The aim of this study was to evaluate the effectiveness of individual placement and support (IPS) for people struggling with work participation due to moderate-to-severe mental illness. The study was conducted in Norway, a setting characterized by a comprehensive welfare system and strong employment protection legislation. ' ' METHODS ': 'A randomized controlled multicenter trial including 410 participants was conducted. The intervention group received IPS according to the IPS manual. The control group received high-quality usual care. The main outcome was competitive employment at 12- and 18-months follow-up, based on objective registry data. Changes in mental health and health-related quality of life were secondary outcomes. ' ' RESULTS ': 'At 12-months follow-up, 36.6% of participants in the IPS group and 27.1% of participants in the control group were in competitive employment, while the difference was slightly higher (37.4% versus 27.1%) at 18-months follow-up. Furthermore, IPS yielded positive effects on all the secondary outcomes compared to the control group (all P<0.05). ' ' CONCLUSIONS ': 'The IPS model of supported employment was superior to high-quality usual care on both vocational and non-vocational outcomes for people with moderate-to-severe mental illness, even in a policy context characterized by high job security and a comprehensive welfare system.
Keywords: depression; employment; individual placement; mental health; mental illness; occupational rehabilitation; patient; psychosis; randomized controlled multicenter trial; randomized controlled trial; RCT; rehabilitation; severe mental illness; supported employment